2023
DOI: 10.1088/1361-6560/acc922
|View full text |Cite
|
Sign up to set email alerts
|

Fluid compartments influence elastography of the aging mouse brain

Abstract: Objective: Elastography of the brain has the potential to reveal subtle but clinically important changes in the structure and composition as a function of age, disease, and injury. 

Approach: In order to quantify the specific effects of aging on mouse brain elastography, and to determine the key factors influencing observed changes, we applied optical coherence tomography reverberant shear wave elastography at 2000 Hz to a group of wild-type healthy mice ranging from young to old age. &#x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
3
1
Order By: Relevance
“…The strongest correlation we found within our set of measurements was the inverse relationship between free water and shear modulus as depicted in figure 4. This negative correlation is most pronounced in the grey matter where greater amounts of extracellular matrix (or glymphatic) free water are associated with softer grey matter, which is consistent with our earlier results both theoretical and experimental (Ge et al 2022(Ge et al , 2023 as detailed in the following section. Moreover, our results suggest a positive relationship between NDI and MD with age and stiffness in grey matter, while FA exhibits a negative correlation with stiffness and age in white matter.…”
Section: Corresponding Mr Measuressupporting
confidence: 92%
See 4 more Smart Citations
“…The strongest correlation we found within our set of measurements was the inverse relationship between free water and shear modulus as depicted in figure 4. This negative correlation is most pronounced in the grey matter where greater amounts of extracellular matrix (or glymphatic) free water are associated with softer grey matter, which is consistent with our earlier results both theoretical and experimental (Ge et al 2022(Ge et al , 2023 as detailed in the following section. Moreover, our results suggest a positive relationship between NDI and MD with age and stiffness in grey matter, while FA exhibits a negative correlation with stiffness and age in white matter.…”
Section: Corresponding Mr Measuressupporting
confidence: 92%
“…There is a profound difference in trendline between the aging effects we found in mouse studies (Ge et al 2022(Ge et al , 2023 and this human study. Earlier experiments found that the mouse brain cortical grey matter stiffens and becomes drier (lower W ) with age, whereas the human brain softens and has a higher water fraction W as a function of age.…”
Section: Of Mice and Mencontrasting
confidence: 72%
See 3 more Smart Citations